In Search of an Identity for the Polish-Russian Border - Domaniewski, Stanislaw K. (International Journal of Contemporary Economics and Administrative Sciences, 2016)
The opening up of borders in Europe since 1989 has created vast possibilities for trade and cultural interaction. The collapse of the Iron Curtain has seen a radical shift in the reconfiguration and re-administration of the European borders landscape. Formerly hostile borders now resemble ever expanding economic and cultural bridges. Great strides have been made towards integration throughout vast areas in both Western and former Soviet Bloc economies (Mazurkiewicz 1992). An interconnected single market has been created where once only barriers existed. Links have been fashioned between countries, societies and individuals. Nonetheless certain border areas are still difficult to access and continue to challenge not only to wider EU economic integration, but also individual aspirations. This paper reflects interviews conducted along the Polish-Russian border near Braniewo in Warmia-Mazury County, Poland. This area still has a militarized and bureaucratic border, requiring individuals to make an effort to access the other side. During individual interviews, conducted in summer 2012, two common themes were expressed. The first was of people making the most of the border which contrasted with others having no desire to cross or know what is on the other side. The first group made a choice to (inter)act and tolerated the current border situation. The second group instead chose to focus their lives inwards away from the border, highlighting the border as a kind of living entity with its own identity. This paper will discuss these themes and how individuals interact because of the existing border. Keywords: Borders, Europe, Poland, Kaliningrad, Borders, Identity